Stereoelectronic Properties of 1,2,4-Triazole-Derived N-heterocyclic Carbenes - A Theoretical Study - Nguyen, Van Ha (H. : ĐHQGHN, 2020)
A theoretical study on stereo and electronic properties of a series of six 1,2,4-triazole-derived carbenes bearing different N4-substituents, namely isopropyl (1), benzyl (2), phenyl (3), mesityl (4), 2,6-diisopropylphenyl (5) and 1-naphthyl (6), has been carried out. Structures of the six carbenes were first optimized using Gaussian® 16 at B3LYP level. Their molecular geometries and electronic structures of the frontier orbitals were examined. The results suggest the similarity in nature of their HOMOs, which all posses s symmetry with respect to the heterocycle and essentially be the lone electron pair on the Ccarbene. Steric properties of the NHCs was also quantified using percent volume burried (%Vbur) approach. The NHC 1 with isopropyl N4-substituent was the least bulky one with %Vbur of 27.7 and the most sterically demanding carbene is 6, which has large 2,6-diisopropylphenyl substituent (%Vbur = 38.4). Interestingly, the NHCs with phenyl and 1-naphthyl N4-substituents display flexible steric hindrance due to possible rotation of the phenyl or 1-naphthyl around the N-C single bond. Beside stereoelectronic properties of the NHC, topographic steric map of their complexes with metal were also investigated.